Answer:
A
Step-by-step explanation:
Im not sure if its correct tho dont quote me on it ;(
<h3>Answer:</h3>
(x, y) ≈ (1.49021612010, 1.22074408461)
<h3>Explanation:</h3>
This is best solved graphically or by some other machine method. The approximate solution (x=1.49, y=1.221) can be iterated by any of several approaches to refine the values to the ones given above. The values above were obtained using Newton's method iteration.
_____
Setting the y-values equal and squaring both sides of the equation gives ...
... √x = x² -1
... x = (x² -1)² = x⁴ -2x² +1 . . . . . square both sides
... x⁴ -2x² -x +1 = 0 . . . . . polynomial equation in standard form.
By Descarte's rule of signs, we know there are two positive real roots to this equation. From the graph, we know the other two roots are complex. The second positive real root is extraneous, corresponding to the negative branch of the square root function.
Answer:
j = -3, -4
Step-by-step explanation:
j^2 + 7j + 12 = 0
(j + 3)(j + 4) = 0
j = -3, -4
Answer:
Common Ratio = 2
Step-by-step explanation:
Emily started with 12 lb at start.
She will double each day
So,
2nd day she will take up weight = 12 * 2 = 24
3rd day she will take up weight = 24 * 2 = 48
and so on
This is a geometric sequence, which is a sequence where each term is found by multiplying the previous term by a constant which is known as the common ratio.
Here, we are multiplying by "2" to get the next term, so we an say the common ratio is "2".
<u>Answer: Common Ratio = 2</u>
Answer: -209
Step-by-step explanation:
Formula for arithmetic progression
= a + (n - 1)d
Since a10 = 1 and d = -6
a10 = a + 9d
a + 9(-6) = 1
a - 54 = 1
a = 1 + 54
a = 55
Therefore, 45th term = a + (n - 1)d
= a + (45 - 1)d
= a + 44d
= 55 + 44(-6)
= 55 - 264
= -209